The neural basis of intuitive approximate number system in board game Go (Baduk) experts - Taeyoung Lee; Hang Joon Jo; Minah Kim; Jun Soo Kwon (Scientific Reports)
Abstract Studies have shown that newborns and nonhuman animals innately estimate quantities using the approximate number system (ANS), raising questions about whether the ANS is a precursor to advanced computational abilities or an independent cognitive function. Professional board game Go players, who can quickly judge territory sizes without explicit calculations, provide a unique insight into the ANS. Using fMRI, we investigated the neural correlates of the approximate number system in professional Go players. Results showed that during the difficult task, professional Go players exhibited significantly increased activity in the right cerebellum compared to the controls, while several parts of the cerebrum were activated during the easy task. The observed activation in the right cerebellum was inversely correlated with the number of years of training required to become professional players. The findings indicate that the ANS is either facilitated by training or reflects an inherent, exceptional ability in certain individuals, suggesting a cerebellar-based alternative to the computational role of the cerebral cortex.